Short-term Effects of Metformin on Cardiac and Peripheral Blood Cells Following Cecal Ligation and Puncture-induced Sepsis - Didari, Tina; Hassani, Shokoufeh; Baeeri, Maryam; Navaei-Nigjeh, Mona; Rahimifard, Mahban; Haghi-Aminjan, Hamed; Gholami, Mahdi; Nejad, Solmaz Mohammadi; Hassan, Fatima Ismail; Mojtahedzadeh, Mojtaba; Abdollahi, Mohammad (Drug Research, 2020)
Aim of the study Sepsis has well-documented inflammatory effects on cardiovascular and blood cells. This study is designed to investigate potential anti-inflammatory effects of metformin on cardiac and blood cells 12 and 24 h following cecal ligation and puncture (CLP)-induced sepsis.Methods For the purpose of this study, 36 male Wistar rats were divided into six groups: two groups underwent CLP, two groups underwent CLP and received metformin, and two groups only received sham operations. 12 h later, 18 rats (half of rats in each of the three aforementioned groups) were sacrificed and cardiac and blood cells were harvested. Subsequently, 12 h later, the rest of the rats were euthanatized. In all harvested blood and cardiac cells, oxidative stress indicators, antioxidant properties, count of blood cells, neutrophil infiltration, percentage of weight loss and pathological assessment were conducted.Results In our experiment, metformin elevated antioxidant levels, improved function of blood cells and percentage of weight loss. Moreover, in the groups which received metformin, oxidative stress and neutrophil infiltration markers were decreased significantly. Moreover, pathological investigations of cardiac cell injury were reduced in the metformin group.Conclusions Our findings suggest that in CLP induced sepsis model, metformin can improve the function of blood and cardiac cells through alleviating inflammation, improvement of anti-inflammation properties, and enhancement of blood profile, and all these effects are more pronounced after 24 h in comparison with 12 h after induction of sepsis.
Keywords: inflammation; cardiovascular pharmacology; antidiabetic drugs; drug research